Mapping knowledge structure and themes trends of cancer-associated fibroblasts: a text-mining study - Cheng, Kunming; Li, Wanqing; Wu, Haiyang; Li, Cheng (Frontiers in Molecular Biosciences, 2023)
Cancer-associated fibroblasts (CAFs) constitute an important component of the tumor microenvironment, participating in various facets of cancer advancement and being recognized as contributors to tumor immune evasion. The role of CAFs in various tumor types has attracted increasing attention recently. In this work, we conducted a comprehensive bibliometric analysis to uncover research trajectories and highlight emerging areas in the field of CAFs. A systematic search was performed within the Web of Science Core Collection to identify articles/reviews on CAFs published between 2000 and 2023. Leveraging advanced bibliometric tools such as VOSviewer, CiteSpace, and online website, we examined and visualized publication trends, geographic contributions, institutional affiliations, journal prominence, author collaborations, and noteworthy references, keywords, and genes. Our analysis included 5190 publications, indicating a rapid growth trend in both annual publications and citations related to CAFs. China and the United States emerged as the foremost contributors in terms of publications, funding agencies, and international collaborations. Breast cancer was the most studied tumor, followed by colorectal cancer, pancreatic cancer, prostate cancer, and gastric cancer. Based on co-occurrence and bursting keywords, we identified the following research topics including immune cells (T cells, B-cells, tumor-associated macrophages), tumor immune microenvironment (antitumor immunity, immune infiltration, immunosuppression), immunotherapy (PD-L1), microRNAs (miRNA), extracellular vesicles (exosome), multiple tumors (pancreatic ductal adenocarcinoma, bladder cancer, head and neck squamous cell carcinoma), antitumor agents (gemcitabine, cisplatin resistance), bioinformatics (pan-cancer), epithelial-mesenchymal transition (stemness), FAPI PET/CT, DNA methylation, etc., may receive sustained attention in the future. Furthermore, TGFB1, IL-6, TNF, TP53, and VEGFA emerged as the top 5 genes that have garnered the greatest research attention in the field of CAFs. The KEGG enrichment analysis highlighted that the top 20 most studied genes were mainly associated with HIF-1 and Toll-like receptor signaling pathways. In sum, our bibliometric analysis offers a comprehensive overview of the research landscape in the field of CAFs. It encompasses the current state, evolving patterns, and prospective avenues of exploration, with special attention to the potential advancements in tumor immune microenvironment.